Service Excellent Berdasarkan Prespektif Islam di Bank Syariah - Kurniawan, Danang (Sharia Faculty Islamic Economic Law Study Department, 2020)
The effort of Islamic banks in creating and maintaining customers to remain satisfied and loyal is to implement service excellence. Descriptive qualitative research methods by reviewing the literature, books, journals and other references related to the research discussion. The results obtained, that the concept of Islamic banking service excellence consists of three aspects, namely aqidah, morals and muamalah. Al-Qur'an has become a guide in conducting Islamic banking services. Employees must also be able to imitate the Prophet in serving customers when trading (Surat al-Ahzab verse 21). Employees must serve customers with a gentle, forgiving, and a strong determination (Surat Ali Imran verse 159). The bank must also apply the method of propaganda Rasulullah SAW in attracting interest, and fostering customers namely Al-hikmah, Al-Mau'idzah bil Hasanah and Al-Mujadalah Bil Hasanah.